Artery Reconstruction in Right Lobe Living Donor Liver Transplantation: Donor-Recipient Vessel Ratio Is Key to Choosing Recipient Artery. Issue 6 (June 2022) - Lin, Shin-Lung; Lin, Ching-Min; Hung, Yu-Ju; Lin, Ping-Yi; Ko, Chih-Jan; Hsieh, Chia-En; Chen, Yao-Li
Abstract : Background: The aims of this study were to investigate if recipient artery choice in right lobe living donor liver transplant affects postoperative complications and discuss solutions accordingly. Methods: Three hundred fourteen right lobe living donor liver transplantation patients were divided into 2 groups: 163 patients using right hepatic artery as the recipient vessel and 151 patients using left hepatic artery as the recipient vessel. Cases involving 2 recipient blood vessels or the use of other blood vessels as recipient vessels were excluded. Results: Overall vascular embolism rate in both groups was 1.3%, and our complication rate was lower than those in previous studies. There was no significant difference in complication rate between the groups, but a significant difference in recipient/donor artery size ratio was noted. Conclusions: Although left hepatic artery's anatomical position makes it less affected by bile duct anastomosis and thus fewer postoperative complications, we believe that the ratio of the donor-recipient blood vessel size and the length of the anastomosis vessel stumps are the key factors that affect the outcome of the vascular anastomosis.